2018
DOI: 10.21577/0103-5053.20180053
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profile and Milk Cholesterol of Crossbred Holstein × Zebu Cows Fed on Whole Cottonseed

Abstract: The objective of this study was to evaluate the effect of whole cottonseed on diets of cows under grazing on fatty acid profile and milk cholesterol. Five crossbred Holstein × Zebu cows were distributed in a 5 × 5 Latin square. Inclusion levels were 0, 6, 12, 18 and 24%. There was a linear decrease in all fatty acids quantified, saturated and monounsaturated (p > 0.05), possibly due to the action of polyunsaturated fatty acids ingested in the diet. There was no influence of treatment on conjugated linoleic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
0
1
Order By: Relevance
“…As in our study, this reduction is associated with a higher proportion of oleic and linoleic acids, demonstrating the deleterious effect of these fatty acids on lipid synthesis. Costa et al (2018) reported a linear reduction of fatty acids from lipid synthesis in an experiment testing levels of inclusion of 0-24% of cottonseed in the diet, however, contrary to the current study, there was no increase in the proportion of oleic acid and linoleic.…”
Section: Discussioncontrasting
confidence: 99%
“…As in our study, this reduction is associated with a higher proportion of oleic and linoleic acids, demonstrating the deleterious effect of these fatty acids on lipid synthesis. Costa et al (2018) reported a linear reduction of fatty acids from lipid synthesis in an experiment testing levels of inclusion of 0-24% of cottonseed in the diet, however, contrary to the current study, there was no increase in the proportion of oleic acid and linoleic.…”
Section: Discussioncontrasting
confidence: 99%
“…Since 2018, a significant amount of research has been published on the analysis of the fatty component of dairy products using GC. These studies illustrate various aspects of studying the fatty component of dairy products, such as the influence of feed type on the fatty acid composition of milk (Costa et al, 2018;Kučević et al, 2019), the importance of polyunsaturated fatty acids for improving the nutritional value of milk (Nguyen et al, 2019;Khosravi et al, 2018), differences in the fatty acid composition depending on the feeding regime of animals (Agradi et al, 2020;Barać et al, 2018;Sacchi et al, 2020), the influence of fat content on the properties of dairy products (Wang et al, 2019;Paszczyk et al, 2020;Ogrodowczyk et al, 2021), etc. Unresolved issues.…”
Section: The Topicality Of the Problemmentioning
confidence: 99%